Acetylcholinesterase Biosensor Based on Functionalized Renewable Carbon Platform for Detection of Carbaryl in Food - Nunes, Erik W. [UNESP]; Silva, Martin K. L. [UNESP]; Rascón, Jesús; Leiva-Tafur, Damaris; Lapa, Rainer M. L.; Cesarino, Ivana [UNESP] (MDPI, 2022)
Enzymatic electrochemical biosensors play an important role in the agri-food sector due to the need to develop sustainable, low-cost, and easy-to-use analytical devices. Such biosensors can be used to monitor pathogens, endocrine disruptors, and pesticides, such as carbaryl, widely used in many crops. The use of renewable carbon (RC) sources, provided from biomass pyrolysis has been often applied in the fabrication of such sensors. This material is a great candidate for biosensor fabrication due to the presence of surface functional groups, porosity, and moderate surface area. This work describes the functionalization of RC material through an acid treatment with a sulfonitric solution HNO3/H2SO4 (1:3) and the resulting material was characterized by scanning electron microscopy. The obtained RC functionalized (RCF) and the acetylcholinesterase enzyme (AChE) were applied in the construction of the electrochemical biosensor on glassy carbon (GC) electrode and used to detect carbaryl in apple samples. The GC/RCF/AChE biosensor was able to detect the carbaryl pesticide from 5.0 to 30.0 nmol L−1, displaying a LOD of 4.5 nmol L−1. The detection of carbaryl in apple samples presented recoveries between 102.5 to 118.6% through the standard addition method. The proposed biosensor is a promising renewable tool for food safety.
Keywords: acetylcholinesterase enzyme; carbaryl; electrochemical biosensor; food safety; renewable carbon